Stand-up that stands out: Analysis of gendered sequences from a Foucauldian perspective - Nur Sürüç Şen (Literacy Trek, 2022)
This article intends to unveil the conceptualization of gender and power dynamics buried in the sequences uttered by Turkish female comedians in their stand-up performances. Investigating ten clips of staged performances, 69 gendered and 28 failed utterances are given a closer look with the help of thematic analysis under in vivo coding framework. Furthermore, the utterances are transcribed and analyzed in line with conversation analysis premises. The findings might shed light upon the content of the instances alongside discursive strategies that the comedians use to tackle gender and power issues. This defined artifact analysis attempts to put forward how the Turkish female comedians place themselves and other women with regards to power dynamics in the society under the roof of their story lines. Basing on their reactions, audiences' attitudes towards the subject matter have been analyzed. In this respect, humor functioned in many ways such as depicting others' expectations and impositions upon women, eradicating passivized roles assigned by the society, and so on. Overall, the analysis demonstrates that humor can have several dimensions, operating as reflecting on the experiences and societal perceptions in the eyes of a woman. Within the analyzed dataset, the instances seem to be unearthing certain patterns and recursive experiences found in the stories of the comedians.